Resilience at work : how to succeed no matter what life throws at you - Maddi, Salvatore R. (AMACOM, American Management Association, 2005)
Resilience is the key not just to coping with unwanted change and stressful circumstances, but to truly thriving in the workplace. Resilience at Work shows readers how to withstand problems large and small, increasing positive attitudes like commitment, control, and challenge, while decreasing those of isolation, powerlessness, and threat. Packed with practical techniques and real-life examples, the book presents resilience as a powerful skill anyone can develop in order to maximize their potential and change their life for the better.